On the Breeding of Bivoltine Breeds of the Silkworm, Bombyx mori L. (Lepidoptera: Bombycidae), Tolerant to High Temperature and High Humidity Conditions of the Tropics - Harjeet Singh; N. Suresh Kumar (Psyche: A Journal of Entomology)
The hot climatic conditions of tropics prevailing particularly in summer are contributing to the poor performance of the bivoltine breeds and the most important aspect is that many quantitative characters such as viability and cocoon traits decline sharply when temperature is high. Hence, in a tropical country like India, it is very essential to develop bivoltine breeds/hybrids which can withstand the high temperature stress conditions. This has resulted in the development of CSR18 × CSR19, compatible hybrid for rearing throughout the year by utilizing Japanese thermotolerant hybrids as breeding resource material. Though, the introduction of CSR18 × CSR19 in the field during summer months had considerable impact, the productivity level and returns realized do not match that of other productive CSR hybrids. Therefore, the acceptance level of this hybrid with the farmers was not up to the expected level. This has necessitated the development of a temperature tolerant hybrid with better productivity traits than CSR18 × CSR19. Though, it was a difficult task to break the negative correlation associated with survival and productivity traits, attempts on this line had resulted in the development of CSR46 × CSR47, a temperature tolerant bivoltine hybrid with better productivity traits than CSR18 × CSR19. However, though, these hybrids are tolerant to high temperature environments, they are not tolerant to many of the silkworm diseases. Keeping this in view, an attempt is made to develop silkworm hybrids tolerant to high temperature environments.